War correspondents reporting from conflictridden parts of the world (Herald of Journalism, 2016)
This article analyses the concept of objectivity is central to all forms of journalism, although its role in traditional war reporting has been a subject of complex and continuous debate. A significant criticism to fundamen- tal journalistic standards is associated with ambiguous levels of neutrality in the coverage of conflicts. War correspondents reporting from conflict- ridden parts of the world tend to draw a moral equivalence between the event’s main victims and culprits, which lead to an abandonment of objec- tivity and impartiality. Consequently, a professional war reporter confronts a serious dilemma in order to portray a fair, balanced and impartial picture of war.
Keywords: оbjectivity; impartiality; ‘journalism of attachment’; War correspondents.